2004
DOI: 10.1007/s00268-004-7602-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Indications for Hürthle Cell Cancer

Abstract: Hürthle cell carcinoma (HCC) has been reported to have variable clinical behavior. The objective of this study was to determine the important prognostic factors in patients with HCC. It was a retrospective investigation of 33 patients with HCC treated in our institution from 1976 to 2002. The average age of our 33 patients with HCC was 55.2 years (range 20-82 years; 23 women, 10 men). Fifteen patients (45.5%) presented with a T2 tumor, 7 (21.2%) with a T3 tumor, and 8 (24.2%) with a T4 tumor; the tumor stage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 38 publications
6
101
3
2
Order By: Relevance
“…By definition, HCN are composed of 75% or more HC and are subclassified as benign (HCA, based on complete fibrous encapsulation and compression of the thyroid parenchyma around the adenoma) or malignant (HCC, based on the presence of capsular invasion, vascular invasion, extrathyroidal tissue invasion, nodal involvement, or distant metastasis) [13,14,15]. HC may also be present in a variety of nonneoplastic conditions such as Hashimoto's thyroiditis, nodular goiter, long-standing Graves' disease, irradiated thyroids, aging thyroids, thyroglossal duct cyst, and other thyroid neoplasms [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…By definition, HCN are composed of 75% or more HC and are subclassified as benign (HCA, based on complete fibrous encapsulation and compression of the thyroid parenchyma around the adenoma) or malignant (HCC, based on the presence of capsular invasion, vascular invasion, extrathyroidal tissue invasion, nodal involvement, or distant metastasis) [13,14,15]. HC may also be present in a variety of nonneoplastic conditions such as Hashimoto's thyroiditis, nodular goiter, long-standing Graves' disease, irradiated thyroids, aging thyroids, thyroglossal duct cyst, and other thyroid neoplasms [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical role of radioactive iodine treatment is largely limited to post-surgical ablation. But many patients have actually received the treatment for metastatic disease, recurrent lesions or small residuals after surgery, and have had a satisfactory effect (8,12), and it has been reported that although radioactive iodine treatment has no survival benefit, it shows better outcomes for adjuvant ablation therapy (13). Hormone withdrawal and recombinant human TSH stimulation have been used with variable success rates.…”
Section: Discussionmentioning
confidence: 99%
“…The peak age of incidence is 50 -60 years (3,6,7). About 20 -30% of the cases had metastatic extension at the time of initial treatment (3,8).…”
Section: Discussionmentioning
confidence: 99%
“…A neoplasia de célula de Hurthle é infreqüente em crianças e adolescentes, ocorrendo geralmente entre a 5 a e 6 a décadas de vida 15 . Lopez-Penabad et al também observaram uma clara diferença de idade em sua série, entre os adenomas e carcinomas, sendo os últimos nove anos mais velhos 4 .…”
Section: Métodounclassified